Public management and sustainable development planning : a model to implement - Dejo, Federico (2013)
One of the least developed aspects of public management, and therefore one of its main weaknesses, is the integral and harmonious management of the State's resources in terms of national development objectives. This is accompanied by the low understanding on the part of political authorities and public officials of the concept of the State as a territorial unit, where the different components of the State are important pieces that form part of a single functional structure.